Pentalogy of Cantrell: Is Echocardiography Sufficient in the Neonatal Period? - Elke Zani-Ruttenstock; Augusto Zani; Osami Honjo; Priscilla Chiu (Georg Thieme Verlag KG, 2017)
Pentalogy of Cantrell is a rare syndrome that is characterized by varying degrees of midline wall defects and congenital cardiac anomalies. A left ventricular diverticulum (LVD) is defined as partial ectopia cordis, can be part of the pentalogy of Cantrell, and can put the patient at risk of severe complications. Early diagnosis and ligation/resection of the LVD is important to prevent complications. We report on a case of pentalogy of Cantrell, in which a LVD was diagnosed only at 2 months of age despite preceding pre- and postnatal echocardiography. We conclude that in the suspicion of pentalogy of Cantrell, either complete or incomplete, cardiac magnetic resonance imaging should be performed, when possible, to avoid the potential complication of a herniating ventricular diverticulum.